Tolerancja jako fundament europejskiej tożsamości - Jasiński, Arkadiusz Mirosław (Refleksje. Pismo naukowe studentów i doktorantów WNPiD UAM, 2018)
Muslim culture in Europe (mainly in the European Union) and the issue of tolerance, which plays a major role in the relationship between different cultures. The main point of this article is to isolate and describe the types of tolerance (and their incentive substrate). What is more an indication of their use in solving problems arising in multicultural societies, as well as outline the substance of the European cultural identity (its advantages and disadvantages, the ratio of “their” and “foreign” to her - consequences resulting from this). An important aspect of this paper is the influx of immigrants from Africa and Near East countries - related problems, conflicts, threats and the perspective of coexistence. The whole discussion is conducted in relation to the position on the “Other” occupied by modern liberal democracy.